A tuneable hierarchical self-assembly of a C3-symmetric triaminoguanidinium-derivative into a rhombic dodecahedral morphology. Issue 31 (30th July 2020) - Dey, Ananta; Maity, Arunava; Singha Mahapatra, Tufan; Suresh, Eingathodi; Mandal, Amal Kumar; Das, Amitava
Abstract : A controllable self-assembly of a small organic molecule produces a crystalline ordered rhombic dodecahedral shape with a size up to 23.7 μm. Crystal structure analysis expounds the growth mechanism for this particular shape evaluation. Abstract : A crystalline rhombic dodecahedral shape with a size up to 23.7 μm via the self-assembly of a C 3 -symmetric triaminoguanidinium derivative has been reported. Structural evidence confirms the preferential occupancy of the solvent molecules in the (110) crystal facet over (100), favouring the growth direction for realizing such morphology.